Reconocimiento de granos de polen de algunas plantas meliferas en la Sabana de Bogota - Ortiz de Boada, D.=700 1 Cogua, J.
(En, Es)
Ilus., 24 ref.
Keywords: PLANTAS MELIFERAS; POLEN; PALINOLOGIA; COLOMBIA; AGRONOMIA COLOMBIANA